From Urban Places to Outdoor Spaces: Field-Tested Practices for Engaging BIPOC Youth and Diversifying Outdoor Recreation - Thomas, Mariko O.; Thomas, Charles H. (Frontiers in Communication, 2022)
This perspective piece offers tools from the field on crucial strategies for successful BIPOC focused outdoor recreation programs. Drawing from applied work in the field, we reflect on the role outdoor nonprofits have played in our family’s relationship with “nature” and what we have learned from work with the Los Angeles based nonprofit Outward Bound Adventures (OBA) about diversifying outdoor recreation. We argue for more inquiries from the communication discipline on racial diversity in the outdoors, and suggest five important strategies to working with youth in outdoor nonprofits. These include: grapple with intersectionality, remind students “nature” is wherever they are, make change intergenerational, apply “forced” opportunity, and hire leaders reflective of the student population. In doing so, we hope to provide groundwork for potential studies from the communication discipline on the overall topic of outdoor recreation and race.